American Society of Regional Anesthesia and Pain Medicine expert panel recommendations on point-of-care ultrasound education and training for regional anesthesiologists and pain physicians—part I: clinical indications. Issue 12 (24th February 2021) - Haskins, Stephen C; Bronshteyn, Yuriy; Perlas, Anahi; El-Boghdadly, Kariem; Zimmerman, Joshua; Silva, Marcos; Boretsky, Karen; Chan, Vincent; Kruisselbrink, Richelle; Byrne, Melissa; Hernandez, Nadia; Boublik, Jan; et al.
Abstract : Point-of-care ultrasound (POCUS) is a critical skill for all regional anesthesiologists and pain physicians to help diagnose relevant complications related to routine practice and guide perioperative management. In an effort to inform the regional anesthesia and pain community as well as address a need for structured education and training, the American Society of Regional Anesthesia and Pain Medicine (ASRA) commissioned this narrative review to provide recommendations for POCUS. The guidelines were written by content and educational experts and approved by the Guidelines Committee and the Board of Directors of the ASRA. In part I of this two-part series, clinical indications for POCUS in the perioperative and chronic pain setting are described. The clinical review addresses airway ultrasound, lung ultrasound, gastric ultrasound, the focus assessment with sonography for trauma examination and focused cardiac ultrasound for the regional anesthesiologist and pain physician. It also provides foundational knowledge regarding ultrasound physics, discusses the impact of handheld devices and finally, offers insight into the role of POCUS in the pediatric population.